Interactions of DNA with H2TMPyP4+and Ru(II)TMPyP4+: Probable Lead Compounds for African Sleeping Sickness (Bangladesh Pharmaceutical Journal, 2015)
Interactions of DNA with free base porphyrin, tetrakis(1-methylpyridium-4-yl)porphyrin (H2TMPyP4+) and its metallo-derivative of ruthenium(II) have been investigated by UV-Vis, fluorescence and circular dichroism (CD) spectroscopy at 0.1 M NaCl, 7.5 pH and 25 °C. The results suggest that Ru(II)TMPyP4+ interacts with DNA via outside binding in self-stacking manner as indicated by UV-Vis data, a small red shift (?? =3 nm) and a minimal hypochromicity (10%) upon addition of DNA. CD spectra showed the presence of a new peak in the Soret region on addition of Ru(II)TMPyP4+ to DNA solution. On the other hand, the interaction of free base porphyrin, H2TMPyP4+ with DNA revealed a significant hypochromicity (30%) and a large red shift (??=20 nm)in the UV-Vis results which conforms intercalation of free base porphyrin with DNA. In this case, the CD results showed only a negative peak developed in the Soret region during titration with DNA. Fluorescence spectroscopy revealed that initially aggregated porphyrin species were de-aggregated after addition of DNA. This phenomenon has been verified with the fluorescence experiments for the porphyrins in the presence of different concentrations of NaCl and ethanol. Ru(II)TMPyP4+ showed enhanced DNA cleavage in the presence of EcoR1 restriction enzyme, where the enzyme did not cleave DNA. Metallo-porphyrins having the ability to cleave DNA could be used as chemotherapeutic agents for the treatment of African sleeping sickness (Trypanosomiasis). DOI: http://dx.doi.org/10.3329/bpj.v17i1.22321 Bangladesh Pharmaceutical Journal 17(1): 79-85, 2014